Elephants on the edge : what animals teach us about humanity - Bradshaw, G. A. (Gay A.), 1959- (Yale University Press, 2009)
Drawing on accounts from India to Africa, California to Tennessee, and on research in neuroscience, psychology, and animal behavior, Bradshaw explores the minds, emotions, and lives of elephants.